Does fasting during Ramadan increase the risk of the development of sialadenitis? - Michael V. Joachim; Yasmine Ghantous; Suleiman Zaaroura; Kutaiba Alkeesh; Tameem Zoabi; Imad Abu el-Na'aj (BMC, 2020)
Abstract Background Ramadan is a month within the Islamic lunar calendar when Muslims are required to fast (abstain from food and drink) during the daytime (from sunrise to sunset) for the entire month. Due to the established connection between fasting and dehydration and acute sialadenitis, the aim of this study is to determine if there is a higher frequency of sialadenitis among the Muslim population during Ramadan than during other months of the year. Methods We conducted a retrospective study using the medical records of 120 Muslim patients admitted to the emergency room (ER) and diagnosed with acute sialadenitis over a 5-year period at the Baruch Padeh Medical Center, Poriya, and St. Vincent de Paul (French) Hospital, Nazareth, both located in Israel. The study group were Muslim patients, with the aforementioned diagnosis, admitted during Ramadan, while the control group included patients diagnosed with sialadenitis during the rest of the year. We analyzed overall admission frequency as well as descriptive and diagnostic data, including age, sex, gland involved and several blood test results. Results During the month of Ramadan, the admission of Muslims with a diagnosis of acute sialadenitis was more than double that during the other months of the year - a difference that was found to be statistically significant (p = 0.001). Additionally, we found that Ramadan sialadenitis patients had significantly higher leukocyte numbers at admission (p = 0.0085) and, importantly, a significantly higher level of dehydration (blood urea nitrogen (BUN)/creatinine ratio) than non-Ramadan sialadenitis patients (p = 0.0001). Conclusion There is evidence that fasting in Ramadan may increase the risk for the development of acute sialadenitis. Our results suggest that this may be the result of dehydration.